ANALISIS PENERAPAN MODEL PEMBELAJARAN WORD SQUARE UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PADA MATA KULIAH PENGANTAR AKUNTANSI - Ade Pipit Fatmawati; M. Rizal Satria (LAND JOURNAL, 2023)
The learning process carried out in higher education cannot be separated from the interaction process between lecturers and students. In practice, the learning process is not easy because students not only capture information from the lecturer, but also other efforts are needed to get good grades. Problems about learning outcomes are generally faced by several students in each department. This happened to 2019’s students in the D4 Financial Accounting study program at the Pos Indonesia Polytechnic, where student learning outcomes in introductory accounting courses were not quite good. In fact, these courses are very important to be studied and used as the basis for courses in future semesters in the accounting department. Several factors may affect the low learning outcomes, such as lack of interest and lack of student motivation in understanding the material presented by the lecturer, so that students are less involved in the learning process, and the learning method used by the lecturer is too monotonous. Therefore, lecturers need a learning model that is not boring so that it can help the class situation to be more active and interesting. One learning model that is interesting and has elements of a game is the word square learning model. Word square learning can make students directly involved in learning activities that are expected to be able to connect knowledge in the context of real world situations. The purpose of this study was to analyze the application of the word square learning model to increase motivation and learning outcomes of accounting students in the Introduction to Accounting course. This type of research uses a quasi-experimental design using the Noneequivalent control group design type. Determination of this type of quasi-experimental research on the grounds that this research is an educational research that uses humans as research subjects.